Nanotechnology applied to packaging production: Review - Oliveira , Jéferson Scott de; Rodrigues, Júlia Abelini; Maestrelli, Sylma Carvalho (Seven Editora, 2023)
In view of the search for intelligent and sustainable packaging, this research aimed to understand how nanotechnology can be used in favor of the production of primary packaging. From the comprehension of the literature on the subject, it was discussed in a qualitative way about the differences between the traditional primary packaging compared to the technological ones and what were the main nanotechnological advances in packaging in recent years. The potential security problems and current legislation were also evaluated, discussing the current scenario and the future perspective in the interim. It could be concluded from the data collected that nanotechnology applied to the production of primary packaging has the potential to bring significant benefits in several areas, such as protection against external agents, sustainability and logistics optimization. However, it is essential to ensure the safety of materials and regulate their use responsibly and, for this, research and development in this area are necessary to overcome the challenges to then start producing nanotechnological packaging on a large scale. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-061